Bureaucracy Pathology on the Regional Secretariat of Makassar City in Providing Service - Rahman Rahman; Andi Asy’hary J. Arsyad (Program Pascasarjana Universitas Negeri Makassar, 2023)
The study focused on how the attitude of the government bureaucracy apparatus in the regional secretariat of Makassar city in providing service to the societies. The study is entitled “The Bureaucracy Pathology in Regional Secretariat of Makassar City in Serving Communities”. The study is expected to give input to the government in evaluating the bureaucracy in the Regional Secretariat of Makassar City. The research aims to describe and explain the attitude of the bureaucratic apparatus in giving service to the community in the Regional Secretary in Makassar City. It is a descriptive study collecting data from two methods: library research and field research. To obtain objective results, data from the field were analyzed qualitatively. Quantitative complementary data were obtained from field reports and notes. Based on the research findings, types of bureaucracy pathologies found in the Regional Secretariat of Makassar City included the apparatus being indiscipline toward the time, they were less responsible, they showed some discrimination, and they were less polite in serving societies